Value-based Mavericking - Maureen P. Molinari; Kara Vander Linden (Grounded Theory Review: An International Journal)
This classic ground theory (CGT) study presents a theory to explain a four-stage process for resolving moral distress encountered in professional environments. Value-based mavericking explains that misalignment between personal and professional values may lead to moral distress and burnout and, that while coping strategies may ease symptoms, the underlying problem still exists. Value-based mavericking presents a process that includes evaluating professional alignment and values and then choosing if and how to continue working in the current professional environment. Following the CGT method, data from primarily healthcare professions were collected. Data were analyzed using coding and constant comparative analysis to develop the theory. Value-based mavericking presents a diferent way of approaching moral distress and burnout that has not been previously addressed in the literature.